2018
DOI: 10.1097/md.0000000000012205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between CT activity score with lung function and the serum angiotensin converting enzyme in pulmonary sarcoidosis on chest HRCT

Abstract: To address the reliability of CT activity score (CTAS) and investigate the relationships between CTAS, lung function changes after treatment and the serum angiotensin-converting enzyme (SACE) levels.Fifty-seven sarcoidosis patients underwent chest high-resolution CT (HRCT) and spirometry, as well as SACE examination, were retrospectively analyzed. Follow-up spirometry in each patient was obtained about 6 months after the initial spirometry. The correlations between CTAS and pulmonary function changes were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A retrospective study of a cohort of 57 patient reproduced these results and found significant correlations with lung function changes after six months of therapy (Change in %VC: r = 0.543, P < 0.001). Furthermore, higher CTAS scores were seen in patients with high sACE levels ( 124 ). Even though the results of these HRCT scoring systems are promising, they are still not widely implemented in standard patient care.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…A retrospective study of a cohort of 57 patient reproduced these results and found significant correlations with lung function changes after six months of therapy (Change in %VC: r = 0.543, P < 0.001). Furthermore, higher CTAS scores were seen in patients with high sACE levels ( 124 ). Even though the results of these HRCT scoring systems are promising, they are still not widely implemented in standard patient care.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…It is produced by lung endothelial cells, mainly activated alveolar macrophages [ 10 ]. It is elevated in serum and BAL of sarcoidosis patients and its concentrations correlate with radiological stages [ 11 13 ]. However, its utility as a diagnostic and prognostic tool is limited by its low sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Our cohort is larger in size than the cohort where peripheral lymphopenia was observed and has a larger proportion of cases with lung involvement [52]. Other potential biomarkers of disease activity such as angiotensin converting enzyme [53,54] and soluble IL-2R levels [55,56] were also not different in treated vs untreated groups or in whites vs. blacks. The higher level of albumin observed in whites and a higher level of total protein in blacks has been reported previously [57] in these racial groups.…”
Section: Discussionmentioning
confidence: 72%